Transparency and Ambiguity in Central Bank Safety Net Operations - Enoch, Charles (IMF Working Papers; Working Paper ;, 1997)
To mitigate the risks of contagion from problems arising in the banking sector, many countries operate some form of banking sector safety net. Such safety nets generally involve a judicious mixture of transparency and ambiguity. This ambiguity may be important to counter moral hazard effects but may lead to excessive forbearance in the face of banking problems. While the scope for ambiguity has been declining, some ambiguity in the handling of individual institutions remains. In any case, ex post transparency is essential for reviewing the propriety of any assistance and preserving the authorities' future reputation and policy credibility.